Materials & skills for historic building conservation - Forsyth, Michael, 1951-; Wiley InterScience (Online service) (Oxford, UK ; Malden, MA : Blackwell Pub., 2008)
Here is provided all the essential information on the properties of traditional building materials. Subjects covered include their availability & sourcing, the causes of erosion & decay, knowledge of the skills required for their application on conservation projects & the impact the materials have on the environment.
The philosophy of repair / Michael Forsyth -- Stone. Types of wall construction / Ian Williams. Oolitic limestone / David McLaughlin. Sandstone / Ian Williams. Granite / Robert Cotta -- Brickwork / Mike Stock -- Lime-based plasters, renders and washes / Rory Young -- Concrete and reinforced concrete / Michael Bussell -- Stone slate, clay tile and metamorphic slate / Christopher Harris -- Cast iron, wrought iron and steel / Geoff Wallis and Michael Bussell -- Understanding decay in building timbers / Brian Ridout -- Timber / Charley Brentnall -- Wattle and daub / Tony Graham -- Sash windows / Gus Astley -- Window glass / Michael Forsyth -- Exterior colour on the smaller town house / Patrick Baty.
Includes bibliographical references and index.
Print version record.
Keywords: Building materials; Historic buildings -- Conservation and restoration -- Materials; TECHNOLOGY & ENGINEERING -- Construction -- General; Modernisierung <Bauwesen>; Baustoff; Electronic books